2015
DOI: 10.1074/mcp.m114.046110
|View full text |Cite
|
Sign up to set email alerts
|

Proteotranscriptomic Profiling of 231-BR Breast Cancer Cells: Identification of Potential Biomarkers and Therapeutic Targets for Brain Metastasis

Abstract: Brain metastases are a devastating consequence of cancer and currently there are no specific biomarkers or therapeutic targets for risk prediction, diagnosis, and treatment. Here the proteome of the brain metastatic breast cancer cell line 231-BR has been compared with that of the parental cell line MDA-MB-231, which is also metastatic but has no organ selectivity. Using SILAC and nanoLC-MS/MS, 1957 proteins were identified in reciprocal labeling experiments and 1584 were quantified in the two cell lines. A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 75 publications
1
61
1
Order By: Relevance
“…The identified protein changes confirm data from our previous proteomic and transcriptional profiling of this cell model (12, 15, 17, 33), and comparison of gene and protein expression datasets allowed the identification of proteins that are either transcriptionally or post-transcriptionally regulated in response to ErbB2 overexpression. The correlation between altered protein and mRNA levels was similar to a previous study investigating a cell model of brain metastatic breast cancer, suggesting that there may generally be a correlation factor close to 0.6 between protein and mRNA in breast epithelial cells (34). Notably, some of the same proteins were altered, possibly implicating their involvement in the molecular mechanisms by which ErbB2-overexpressing breast tumors metastasize to the brain.…”
Section: Discussionsupporting
confidence: 83%
“…The identified protein changes confirm data from our previous proteomic and transcriptional profiling of this cell model (12, 15, 17, 33), and comparison of gene and protein expression datasets allowed the identification of proteins that are either transcriptionally or post-transcriptionally regulated in response to ErbB2 overexpression. The correlation between altered protein and mRNA levels was similar to a previous study investigating a cell model of brain metastatic breast cancer, suggesting that there may generally be a correlation factor close to 0.6 between protein and mRNA in breast epithelial cells (34). Notably, some of the same proteins were altered, possibly implicating their involvement in the molecular mechanisms by which ErbB2-overexpressing breast tumors metastasize to the brain.…”
Section: Discussionsupporting
confidence: 83%
“…S3 and S4). However, as the available breast cancer cell lines, including metastatic breast cancer cells, differ in their biological and genetic makeup, a detailed investigation of the cell‐type specific behavior would be needed while adapting this platform to study the underlying mechanobiology . In addition to adhesion, spreading, and proliferation, we showed that the MDA‐MB‐231Br single cell migration is regulated by matrix stiffness (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Finding Needles in Haystacks: The Use of Quantitative Proteomics for the Early Detection… DOI: http://dx.doi.org /10.5772/intechopen.80942 Acronyms and abbreviations cancer/carbohydrate antigen 19…”
Section: Discussionmentioning
confidence: 99%
“…Over the last 2 decades, unprecedented technological advancement in proteinbased mass spectrometry (proteomics) has radically changed the landscape of biomarker research [13] (Table 1). This has facilitated the characterization of complex cellular proteomes [14][15][16][17][18][19], research that has identified hundreds of over and under expressed proteins in carcinoma patients using tumor tissue, histological sections, plasma or fecal samples when compared to matched normal tissues [20][21][22][23][24]. Despite this, with the exception of Carcinoembryonic antigen (CEA) and Cancer antigen [25], no new protein biomarkers have made it into routine clinical practice [21,26,27].…”
Section: Introductionmentioning
confidence: 99%